The Influence of Carbon, Phosphorus, Manganese and Sulphur on the Tensile Strength of Open-Hearth Steel - H. H. Campbell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
MANY attempts have been made to write a formula by which to calculate the strength of steel from its chemical composition, but most of these endeavors have failed because there were too many disturbing conditions. It is idle to collect from the pages of trade-papers, books, or the proceedings of scientific societies, a multitude of observations. The combination of such results will simply show that steel of the same composition will vary in tensile strength through wide limits-a fact that has been known for generations. That cold-working, overheating, and many another form of heat-treatment alter fundamentally the strength of steel, is ancient history, although it is only recently that the microscope has pointed out the road to an explanation of the phenomena. It may be urged that the microscopic structure must be taken into consideration in any formula giving the ultimate strength, but from the standpoint of the present investigation this is unnecessary. We are trying to determine primarily, not what changes in ultimate strength may be made by variations in the condition of carbon, but what effect is produced by changes in the amount of carbon, when its condition remains constant. For such an inquiry, in order that the condition of the carbon should remain as nearly uniform as possible, it is essential that all test-pieces be made under the same conditions; and it is be¬lieved that the tests described in this paper satisfy that require¬ment. The investigations were made at the works of the Pennsylvania Steel Company,. Steelton, Pa.; the ingots from which the tests were made were 6 in. square in every case; they were heated in the same furnace and forged at the same ham